Station‐Based Assessment of Sub‐Seasonal Climate Trends in the Tyrolean Alps (Austria) - Erwin Rottler; Elena Bertazza; Franz Wagner; Gertraud Meißl; Theresa Schellander‐Gorgas; Johannes Schöber; Ulrich Strasser (International Journal of Climatology, 2026)
The assessment and understanding of climatic changes in mountain regions with complex topography, and their impact on snowmelt and river runoff, are of great importance for the water supply worldwide. Analyses based on observations from high alpine monitoring networks are crucial in this regard. This study quantifies the magnitude and significance of climate trends on the sub‐seasonal scale across elevations by compiling and processing measurements from multiple meteorological station networks in the Tyrolean Alps (Austria). We processed time series from more than 300 locations, of which 86 had records long enough to be included in the trend analysis. Our analysis indicates a warming rate of 0.43°C/dec over 1964–2023 (mean across 27 homogenised time series), with stronger warming in recent decades and greater sub‐seasonal trend variability when shortening the analysis window from 60 to 30 years. Similar sub‐seasonal trend patterns also appear in snow and discharge data sets. Between 1994 and 2023, elevation‐dependent differences in temperature trends emerge in January, with warming at low elevations and slight cooling at high elevations. Analyses of hourly precipitation indicate a tendency towards more hours of heavy rainfall in summer. Our study provides a systematic comparison of multi‐variate observations from multiple data providers in complex mountain terrain, offering new insights into sub‐seasonal and elevation‐dependent characteristics of climate change.

Does meter-scale snow data matter for modeling alpine plant distribution? A comparison of four data sources at two resolutions - Andreas Kollert; Kryštof Chytrý; Norbert Helm; Karl Hülber; Dietmar Moser; Johannes Wessely; Stef Lhermitte; Simon Gascoin; Andreas Mayr; Patrick Saccone; Johannes Hausharter; Michael Warscher; et al. (Ecological Modelling, 2026)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Modelling forest snow processes with a new version of WaSiM - Kristian Förster; Jakob Garvelmann; Gertraud Meißl; Ulrich Strasser (Hydrological Sciences Journal, 2018)

Messung molekularer Interaktion mit dynamischen Oberflächensensoren - Ralf Strasser; Dirk Scholl; Paul Hampel; Andreas Langer; Ulrich Rant (BIOspektrum, 2012)